COMPARING THE INCIDENCE AND RISK FACTORS ASSOCIATED WITH CORONARY ARTERY DISEASE IN PATIENTS RECEIVING BRUTON'S TYROSINE KINASE INHIBITORS - Niharika Baviriseaty, MD (Elsevier, 2024)
Therapeutic Area: ASCVD/CVD in Special Populations Background: Bruton's tyrosine kinase inhibitors (BTKi) have increased risk of cardiotoxicity including atrial fibrillation and hypertension. However, little data exists on the incidence and risk factors associated with coronary artery disease (CAD) for patients on BTKi. Methods: This was a retrospective single-center study of patients with hematologic malignancies from 2014-2024 on ibrutinib, acalabrutinib, or zanubrutinib. Patients meeting the following criteria were included: age >65 years, BTKi usage >28 days, and CAD. We measured demographics as well as characteristics of CAD including diagnosis modality, obstructive vs non-obstructive disease, revascularization approach (if any), and medical treatment. Categorical variables were analyzed via chi-squared tests at a significance level of 0.05. Results: Of 534 screened patients, 69 met inclusion criteria. Average age was 76, and 19% were female. Overall prevalence of CAD ranged from 7-15% among the selected BTKi's, with no statistical difference in the prevalence (p=0.24) or incidence of CAD (p=0.69). In sub-group analysis of ibrutinib, hyperlipidemia was associated with new-onset CAD (p=0.04). Only 80% of patients were receiving a statin, with no significant difference between the different BTKi's (p=0.59). Patients on ibrutinib were less likely to be on aspirin compared to those on acalabrutinib (32% vs 63%; p=0.02). Conclusions: Patients with CAD and hematologic malignancies receiving BTKi's appear to tolerate these therapies without excess coronary disease. A prior diagnosis of CAD may not limit BTKi use when indicated. Due to the small sample size, further research is needed to confirm our findings.